El arbitraje internacional de inversiones y la «defensa» de los Estados en nuestros tiempos, ¿necesidad de reforma del sistema? - Delgado Mondragon, Mayra Alejandra (2022)
The purpose of this research is to analyze the main criticisms of the Investor-State Dispute Settlement System, in a context of debate on the reform of the investment arbitration system. There is a more extreme position, which seeks the disappearance of ad hoc arbitration in favor of a new system with a court of appeals or a multilateral investment court. This proposed change reflects the European Union's position on investment dispute settlement mechanisms. Likewise, the research identifies three variables to consider regarding the relevance of establishing a multilateral investment appeal or court mechanism and analyzes a series of operational aspects in relation to the potential establishment of a permanent appeal or court mechanism, as well as considerations related to the decision-makers, should this proposal becomes a reality. Finally, we will point out the practical implications of the debate on the reform of the investment dispute settlement system and its importance for our country.